The effect of moderate physical activity on NK cells populations and cytotoxic T lymphocytes in young, healthy women - Anna Tubek-Krokosz; Jarek Baran; Andrzej Galbarczyk; Adrianna Gałuszka-Bulaga; Magdalena Klimek; Karolina Krzych-Miłkowska; Karolina Leś; Kinga Słojewska; Monika Ścibor; Grazyna Jasienska (PLoS ONE, 2026)
Background Physical activity is a modifiable lifestyle factor known to reduce the risk of many diseases, including cancer, partly through improvement of immune function. Physical exercise activates innate and adaptive immunity, boosting the circulation and function of NK cells and cytotoxic T lymphocytes, key players in cancer surveillance. This study aims to assess the effect of moderate physical activity on NK cells, their subpopulations, and cytotoxic T lymphocytes, in young, healthy women. Methods The study included 141 healthy women aged 20–36. Physical activity was monitored using Fitbit accelerometers over two menstrual cycles, during which participants performed at least 180 minutes/week of moderate physical activity. Blood samples were collected to assess cytotoxic T lymphocytes, NK cells, their subpopulations, and NK cytotoxic activity via flow cytometry. Associations between physical activity and immune parameters, adjusting for age and body fat percentage, were analyzed by multiple linear regression models. Results A higher number of steps per day was positively associated with the proportion of CD56 bright CD16 + NK cells (β = 0.22, p = 0.016), and minutes spent fairly active per day showed a positive association with CD56 bright CD16 − NK cells (β = 0.17, p = 0.051). Higher number of very active minutes per day was associated with stronger natural killing ability of NK cells (β = 0.27, p = 0.030) and with a smaller percentage change between natural and IL-2-activated cytotoxicity (β = −0.25, p = 0.048). No significant associations were observed for total NK cells or cytotoxic T lymphocytes. Conclusions A longer-term moderate physical activity in healthy young women may enhance CD56 bright NK cell subpopulations and natural NK cell cytotoxicity, while reducing responsiveness to IL-2 stimulation. Our findings provide insight into a better understanding of how physical activity affects immune functioning, which might be relevant for cancer prevention, including breast cancer, in healthy women.